PERANCANGAN SISTEM MANAJEMEN BATERAI PADA MOBIL LISTRIK STUDI KASUS: BATERAI KAPASITAS 46Ah 12V PADA NEO BLITS 2 - Luthfitaris Haidiazi Soehartono; Akhmad Musafa; Sujono Sujono (MAESTRO, 2020)
In this paper a battery management system for electric cars has been designed case study: 46Ah 12v capacity kapasias on neo blits 2. The purpose of this system is to protect the battery from overcharge and overdischarge so that the battery will better use its life cycle. With the use of a better life cycle will reduce maintenance costs on electric cars. The system is designed to consist of 84 3.7 volt 2200 mAh parallel Lithium ion batteries 21 and then in series of 4 so that it produces a voltage output of 14.8 volts 46Ah, 1 unit of DC DC converter, 1 unit of arduino mega 2560 microcontroller board, 6 units of voltage sensors , 1 current sensor, 5 temperature sensors, 1 microsd card module, 1 bluetooth module, 1 android smartphone, 1 unit relay module, 1 unit fan, DC motor, DC motor rotation manual module and 1 12v charger unit. How this system works, the battery circuit produces a voltage that is connected to the charger when the charging process and DC motor when the discharging process will be detected by a voltage sensor, as an analog signal input to the arduino mega 2560 microcontroller. Where the switching algorithm in the microcontroller will produce a HIGH or LOW signal as input relay circuit to cut off the current flowing into the battery during the charging process and cut off the current flowing to the DC motor load when discharging. The detection of voltage on each battery cell is displayed via a smartphone. From the discharging process test data the most efficient results are at 135 degrees rotation with the resulting time being 14 hours 46 minutes.